Occurrence of Aelurostrongylus abstrusus and Troglostrongylus brevior in domestic cats in Greece. Issue 1 (December 2015) - Diakou, Anastasia; Di Cesare, Angela; Barros, Luciano; Morelli, Simone; Halos, Lenaig; Beugnet, Frederic; Traversa, Donato
Abstract Background Despite the evidence that Mediterranean Europe offers suitable conditions for the biology of felid respiratory metastrongyloids, no updated data on the presence of felid lungworms are available for Greece. Although the cat lungwormAelurostrongylus abstrusus is considered as enzootic in domestic cats (Felis silvestris catus ) living in some areas of continental Greece, conversely, Troglostrongylus brevior, has only been reported in the island of Crete. The present study aimed to evaluate the occurrence ofAelurostrongylus abstrusus andTroglostrongylus brevior in domestic cats from four different Greek locations including islands where European wildcats (Felis silvestris silvestris ), believed to be the natural reservoir ofT. brevior, are considered absent. Methods Faeces were collected from 125 stray cats in the city of Athens, and in Crete, Mykonos and Skopelos Islands, and examined by copromicroscopic techniques for the presence of lungworm larvae. When present, larvae were morphologically and molecularly identified. Results The occurrence ofA. abstrusus andT. brevior was confirmed in 10 (8 %) and 7 (5.6 %) of the samples, respectively. In particular, T. brevior was detected in domestic cats in the city of Athens, and in Mykonos and Skopelos Islands, where wildcats are not present. Conclusions This information illustrates thatT. brevior may infect domestic cats regardless of the presence of the natural host. Considering the relevant clinical impact of this nematode especially in young animals, it is advisable to include troglostrongylosis in the differential diagnosis of cat respiratory diseases also where this parasite is unexpected.